Reducing the Mortality Gap in People With Severe Mental Disorders: The Role of Lifestyle Psychosocial Interventions - Barber, Sarah; Thornicroft, Graham (Frontiers in Psychiatry, 2018)
This mini-review considers the mortality gap in persons with severe mental disorder (SMD) globally. Current estimates of 10-20 years of potential life lost may be too conservative, both in high (HIC) and low and middle-income countries (LMICs). There is an emerging consensus that natural causes account for the majority of deaths in persons with SMD in both resource settings. In HICs, cardiovascular causes predominate, and can be attributed to individual, health-system and societal level risk factors. Psychosocial lifestyle interventions target behaviour specific risk factors for physical ill-health. There is good evidence for tailored weight-loss programmes, but mixed evidence for smoking cessation, substance misuse and risky sexual behaviour. In terms of supporting persons with SMD, nurse-led services and the utilisation of peer-support are showing promise. Future research efforts must focus on effective interventions and health system models for both high and low resource settings to address this startling health inequality.